To complete the square for the equation \(x^2 + 12x - 14 = 0\), follow these steps:
-
Start with the equation: \(x^2 + 12x - 14 = 0\)
-
Rearrange it to form: \(x^2 + 12x = 14\)
-
To complete the square, we need to add a value to both sides. This value is derived from taking half of the coefficient of \(x\) (which is 12), squaring it, and then adding it to both sides: Half of 12 is 6, and squaring it gives us \(6^2 = 36\).
-
Fill in the blanks: \(x^2 + 12x + 36 = 14 + 36\)
-
This simplifies to: \((x + 6)^2 = 50\)
-
To solve for \(x\), we need to take the square root of both sides: \(\sqrt{(x + 6)^2} = \pm \sqrt{50}\)
-
This results in: \(x + 6 = \pm 5\sqrt{2}\)
-
Finally, isolate \(x\): \(x = -6 \pm 5\sqrt{2}\)
Therefore, the final answers are:
- \(x_1 = -6 + 5\sqrt{2}\)
- \(x_2 = -6 - 5\sqrt{2}\)
Here is the completed summary of the process:
- Start with \(x^2 + 12 - 14 = 0\).
- Rearrange to \(x^2 + 12x = 14\).
- Complete the square: \(x^2 + 12x + 36 = 14 + 36\).
- Factor: \((x + 6)^2 = 50\).
- Take the square root: \(x + 6 = \pm \sqrt{50}\).
- Isolate \(x\): \(x = -6 \pm 5\sqrt{2}\).
- Solutions: \(x_1 = -6 + 5\sqrt{2}\), \(x_2 = -6 - 5\sqrt{2}\).